Decolonizing Indigenous Educational Policies (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2017)
The paper addresses three educational policy documents created by the Ontario Ministry of Education and the Ontario Ministry of Advanced Education and Skills Development (formerly known as the Ontario Ministry of Training, Colleges and Universities [MTCU]) to target and minimize the ‘achievement gap’ of Indigenous children and youth. The policy documents come at a critical time in which statisticians predict a significant increase in Indigenous populations across Ontario as well as Canada (MTCU, 2011). We critique the policy documents, which represent tools of neo-colonialism maintaining dichotomous power relations in which Indigenous communities are positioned as dependent on the white settler Canadian state as providers. Through an anti-colonial theoretical framework, we interrogate the self-purported altruism on behalf of the Canadian government toward Indigenous education initiatives; which mask the neo-liberal agenda of ensuring that the increasing Indigenous populations are conforming to the competitive demands of the market-economy